Analysis Of Control and Accountability in The Process of Physical Training of Young Athletes - Salimov. G’.M. (Genius Journals, 2021)
The leading factor in the implementation of pedagogical control is the provision of complete information about the prerequisites, deployment and results of the pedagogical process. The main requirements for control and accounting are: timeliness and objectivity, accuracy and reliability, completeness and information content, simplicity and clarity. The results of medical examinations of athletes are recorded in the protocols, and on their basis a conclusion is made about the tolerance of the training load; it is indicated what effect the lesson has, whether the load corresponds to the training period; an assessment of the level of functionality is given; a correction is made totraining plans
Keywords: Physical condition; specific facts; psychological control; coach